Strengthening Teaching Materials on the Topic of Adsorption and Metal Analysis by Voltammetry with the STEM Approach - Muliadi, Muliadi; Liestianty, Deasy; Widiantoro, Aldy; Reskika, Sari (Universitas Khairun, 2025)
Strengthening the content of STEM-based teaching materials on adsorption and metal analysis materials by voltammetry is one of the effective and relevant strategies in improving the quality of chemistry learning in higher education. The approach bridges the gap between theory and practice for students. The integration of the STEM approach allows students to understand chemical concepts more deeply and applicatively, as well as improve critical thinking and problem-solving skills. The results of the validity test obtained an Aiken's value of 0.91 with a high feasibility (validity) category. This study aims to develop chemistry teaching materials content based on the STEM approach integrated into adsorption and voltammetric metal content analysis materials. Specifically, the objectives of this study include: (a) analyzing students' learning needs related to understanding adsorption and voltammetry materials; (b) designing and developing STEM-based teaching materials that integrate aspects of science, technology, engineering, and mathematics contextually and applicatively; (c) implementing the developed teaching materials in chemistry learning at the college level.